G62(P) A critical appraisal of the literature on the benefits of gastrostomy feeding, compared to oral feeding, in children with cerebral palsy. (27th April 2015) - Mehta, P; Acerini, C
Abstract : Aims: To assess whether gastrostomy is a beneficial intervention for feeding children with cerebral palsy, compared with only oral feeding, for: promoting growth and weight gain in children who have dysphagia and inadequate nutrition; and improving the quality of life of the children and their families and carers. Methods: A literature search, with strict inclusion criteria, was done of the Cochrane Library, PubMed, and NICE guidelines, and articles were cross-referenced. The articles included were then critically appraised. Results: There are currently no evidence-based clinical guidelines to advise doctors, patients and their families appropriately about oral feeding versus gastrostomy feeding for children with cerebral palsy. Analysis of the articles included in this review consistently supported gastrostomy as being beneficial compared with oral feeding for most, though not all, of the children in these studies, and their families. Nutritional status, subcutaneous fat deposition, weight gain, limb growth, and the number of hospital admissions for chest infections improved in children with gastrostomy tube insertion, and this improvement was significant and clinically important. Moreover, the majority of carers reported that, after gastrostomy insertion, children felt better, were more sociable, had improved general health, and that family life was improved with feeding being made easier and quicker. Conclusion: Gastrostomy tube feeding remains an important alternative nutritional source for children with cerebral palsy. It has consistently been shown to be beneficial at improving not only weight gain and growth, but also the quality of life for both the child and their carers in the long-term. However, there has been individual variability with regard to carers' perceptions of gastrostomy feeding, and mothers can often initially express a feeling of culpability for their child's poor growth and the need for gastrostomy surgery as a failure on their part. Each case needs to be viewed in the context of the social and cultural belief systems of each child's family, and multi-disciplinary support is therefore needed in order to help families with the decision-making process on a case-by-case basis. Furthermore, in the absence of guidelines currently, clinicians must be aware of the current "best evidence" to inform individual choice on gastrostomy as an aid to feeding.